BEDAH AKAD PEMBIAYAAN, PENYUSUNAN GUGATAN BIASA DAN GUGATAN SEDERHANA MELALUI PENGADILAN - Sugeng Riyadi; Endang Eko Wati; Fetri Fatorina; Chamid Sutikno (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The growth and development of Islamic Financial Institutions (LKS) in Indonesia is increasing rapidly. The rapid development of Islamic banking and financial institutions has implications for the greater possibility of problems or disputes arising between service providers and the people served. Sharia Economic Dispute Resolution is a dispute in the field of Islamic economics between Islamic financing institutions and their customers. Then, Islamic Banks resolve this dispute to a litigation institution (Religious Court). But sadly, not all cases of sharia economic disputes are immediately granted by the panel of court judges. The weak content of the lawsuit filed with the religious court is a strong reason for the Religious Court to reject a case filed by an Islamic financial institution. The method used in the implementation of this community service is the method of observation and active participation. The result of the implementation of this community service is an ordinary lawsuit, and a simple lawsuit is a lawsuit that is easy to understand and easy to make. In making ordinary lawsuits and simple lawsuits, accuracy, foresight, and critical reasoning are needed in capturing and understanding sharia economic dispute cases that will be submitted to the Religious Courts. It takes a strong understanding of the substance of the contents of the lawsuit that will be submitted to the Religious Courts. Not only understanding the substance of the concept and making the contents of ordinary lawsuits and simple lawsuits that must really be mastered. But there are other substances that must also be mastered. This substance is an understanding of the concept of the financing contract that is applied along with the risks that will occur. A strong understanding of the substances that must be mastered closes the possibility of a lawsuit being rejected before a panel of judges at the Religious Court as the final decision on the sharia economic dispute at hand.